Budaya Organisasi dan Keterlibatan Kerja terhadap Komitmen Organisasi Berdampak pada Kinerja Karyawan pada BTN â Ciputat - Logahan, Jerry Marcellinus; Aesaria, Sherley Marcheline (Binus Business Review, 2014)
PT. Bank Tabungan Negara, Tbk Ciputat branch is a company engaged in banking in Jakarta. As todays business competition, companies are competing to attract the attention of customers to use the services provided by PT. State Savings Bank, Tbk Ciputat branch. The purpose of this study was to determine the effect oforganizational culture and job involvement on organizational commitment and its impact on the performance of employees at PT. State Savings Bank, Tbk Chester branch. The method used in this study is a path analysis. From the results of the data is found, the organizational culture has not been able to provide significant influence on organizational commitment while job involvement has a significant influence on organizationalcommitment. The next finding was found that organizational culture has a significant influence on employee performance. Later, it was found that job involvement has also a significant influence on employee performance. Furthermore, job involvement simultaneously influences organizational commitment. It was also found that organizational culture and job involvement simultaneously effect on the performance of employees at PT. Bank Tabungan Negara, Tbk Ciputat branch.